The effects of different concentration of ficus deltoidea var. Angustifolia fruits hexane extract on the quality and quantity of mouse oocyte / Nurafida Zamhari - Zamhari, Nurafida (Faculty of Applied Science, 2008)
Ficus deltoidea var. angustifolia is known as Mas Cotek and established as a herbal medicine to heal many diseases such as high blood pressure and gout. It also used as a health tonic and female viagra. The purpose of this study is to investigate the effects of F.deltoidea fruit extracts on the quality and quantity of mouse oocyte. Different concentrations of fruit extracts were used to investigate of these effects. The treatment process was done in five groups according to the concentration of the extracts. Mice of ICR strain was used in this experiment. Mice are common experimental animals in biology and psychology primarily because they are mammals, and thus share a high degree of homology with humans. The quantity of mouse oocyte was determined by counting the number of oocyte under stereoscopic microscope. The quality of oocyte was determined based on the oocyte morphology, size and cumulus intactness. Oocytes collected from ampulla region were transferred to the respective media and observed under microscope. The results showed that increased in concentration of F.deltoidea extracts could decreased the number of mouse oocyte present. It also showed that as the concentration of extracts increased, it could decrease the number of normal oocyte present and decrease the cumulus intactness over oocytes.